An Assessment of the Factors Determining the Development and Sustainability of the Transport Industry and Their Interrelationships: The Case of Lithuania - Jonas Matijošius; Kristina Čižiūnienė; Rytis Zautra (Future Transportation)
The transportation sector is encountering escalating issues associated with technical progress, environmental laws, economic upheavals, and deficiencies in personnel capabilities. Although prior research has examined these concerns separately, there is an absence of thorough studies investigating the interaction between these elements and their influence on the long-term sustainability of the transportation industry. This study aims to address this research vacuum by providing a comprehensive examination of the impact of technical breakthroughs, environmental requirements, supply chain obstacles, and worker skills on the advancement and sustainability of the transport sector. This research employs expert assessment and regression analysis to investigate data from important stakeholders in the transport industry, aiming to elucidate the interrelationships among these four parameters. The results demonstrate a robust association between technical progress and environmental restrictions, while also underscoring considerable economic challenges, especially supply chain disruptions that impede the adoption of new technology. The lack of trained labour is seen as a significant element that intensifies these issues. This study enhances the current literature by providing a comprehensive view of the elements influencing the sustainability of the transport industry. The report offers actionable suggestions for industry stakeholders, including measures to improve staff training, streamline supply chain management, and more efficiently incorporate new technology. These results have considerable significance for governments and transport corporations aiming to secure the industry’s long-term sustainability.